Water Quality on the Growth Performance of Clarias gariepinus in Fish Farms within Fako Division, Cameroon - Nchegang, Benjamin; Enow, Tabe Maxwell; Nkongho, Geneva Ojong; Tan, Paul Vernyuy (Geography, Earth Science and Environment: Research Highlights Vol. 9, 2025)
Fish need a decent environment for their living and livelihood. Fish species that have additional organs as a means of breathing, such as catfish, can tolerate fairly extreme water conditions, but in order to develop optimally, water quality parameters need to be within their recommended ranges. Aquaculture in South-West Cameroon has evolved, although not exponentially, due to a qualified workforce. The problem of water quality in fish farms, which could be associated with poor feeding and water quality management, impacts the life of aquatic animals. Fish need a healthy environment for their optimal growth and development (case study of Catfish). The objective of this study was to determine the impact of water quality on the growth performance of Clarias gariepinus in some fish farms within Fako Division-South West Region of Cameroon. Material and methods: The method used in this research topic is descriptive, with 4 different localities, namely IRAD Batoke (A), Bakingili (B), Cornelius Fish Center (C) and Oumarou fish farm (D), Mile 2 Limbe. A collection of physicochemical and biological data was conducted from the period of March 8th to May 15th 2023, in Fako Division. The data collection was done from Tuesday to Friday, a day each per farm from 7- 8 am. Results: The results revealed the highest mean temperature value (28.22±0.94ºC) in IRAD Batoke broodstocks tanks, while Cornelius Fish Center had the highest mean pH, electrical conductivity, and total dissolved solid with values of 8.16±1.25; 0.84±0.35 ms/cm; and 0.38±1.8ppt in the broodstocks tanks and table fish tanks. The highest dissolved oxygen (<8 mg/l), the highest nitrite level (<0.025 mg/l) and the highest Ammonium (<0.05 mg/l) were noted in three localities except the Bakingili locality. The physicochemical parameters of water had no negative impacts on the growth performance of this species. Conclusion: The results of physicochemical parameters such as water temperature, pH, and electrical conductivity, total dissolved solids, NH4, NO2 and O2 obtained during the study experienced a relative variation and were very suitable for the growth and development of Clarias gariepinus. The study concluded that although the African catfish can tolerate poor water conditions, optimal water quality is crucial for its optimal growth and development. These findings are relevant to the fish production sector for the sustainable production of African catfish.